An empirical-statistical model for runout prediction of debris flows in four geothermal steam fields - Taguines, Jerrence S.; Zarco, Mark Albert H. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Geothermal steam fields are exposed to different types of geologic hazards, among which are debris flows. Debris Flows are considered as a very rapid to extremely rapid surging flow of saturated non-plastic debris within a steep or relatively steep channel. This geologic hazard may cause damage to property (esp. high-value assets), disrupt steam field operations, and even lead to loss of lives. Since the time of Heim (1932), many empirical-statistical models have been developed to assess and predict travel distance of debris flows based on field observations and analysis of various parameter relationships characterizing landslide volume, travel path with the presence of obstruction and morphology, and distance travelled by debris. Researchers on debris flows such as Corominas (1996), Rickenmann (1999), Finlay et al. (1999), and Hunter and Fell (2003) have analyzed significant number of data by means of simplified plots and regression equations. Their data are composed of landslides triggered by heavy rains on countries, mostly, with Mediterranean and humid continental type of climate such as Spain, Canada, Switzerland and the likes. Due to the likelihood of debris flow occurrence in geothermal steam fields, an empirical-statistical research is needed for rapid assessment of exposure to debris flow hazards in four (4) geothermal steam fields situated in Albay and Sorsogon (Bicol), Negros Oriental, Leyte, and North Cotabato in the Philippines. Information on different mobility parameters of debris flow were extracted from sources which include topographic and as-built maps, orthorectified aerial images, and assessment reports for historical data. Mobility parameters considered in this study include estimated debris volume, height of vertical drop, reach angle, and observed travel Distance. Total population sampling was used in this study. From the 57 debris flow events, different data distributions were established. These include 80% training and 20% testing data, 75% training and 25% testing data, and 70% training and 30% testing data distribution. The training data were used to develop the models while the testing data were used to verify the results of the training data. Using simplified plot and regression analysis, an empirical-statistical model from the training data was established through the formulation of regression line equations. The developed models from the training data were then verified using the testing data based on their respective data distributions. Paired t-Test was done using the means of the observed travel distance and the predicted travel distances from the developed models. This was conducted in order to verify if there will be significant difference on the predicted data from the observed data. Furthermore, Normal Probability Plots of the residuals were developed to check if the difference between the observed and predicted distances will not deviate from the normal distribution. Lastly, assessment on the applicability and accuracy of established models from other researchers was relative to the empirical-statistical model derived from this study.
Thesis (Master of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Debris avalanches -- Mathematical models